The Impact of Advertisement on Alcohol Consumption: A Case Study of Consumers in Bantama Sub-Metro - Amoateng, Frank; Poku, Kofi (International Review of Management and Marketing, 2012)
The general focus of the study was to investigate the impact of advertisement on alcoholic beverage consumption at Bantama Sub-Metro in Kumasi. Objectives were to analyse the nature of advertisement of alcoholic beverages, determine factors that influence the consumption of alcoholic beverages and to examine the influence of advertisement on the consumption of alcoholic beverages. A convenient sampling, which is a non-probability sampling, was used to select 220 respondents for the study. Instruments used to collect data were questionnaires. Regression analysis was used to establish the relationship between advertisement and alcohol consumption, which indicated a highly positive correlation. It was revealed that electronic medium was the biggest vehicle through which adverts of alcoholic beverages reach consumers. Again, consumers were more attracted to adverts that made bare the product functions or performances and musicians made the highest impact on consumption patterns of consumers among the celebrities used in adverts of alcoholic beverages among others. The alcohol brewing industries in order to assert themselves well and widen the scope of their products to their target consumers should endeavour to sponsor public events. Keywords: Advertisement; alcoholic beverage; impact; consumption; consumers. JEL Classifications: M37